COVID-19 Disease on 700 Chronic Dialysis Patients from Ecuadorian Highlands: An Observational Study - Juan, Santacruz; Ana, Vasquez; Paulo, Reinoso; Carlotta, Sulbaran; Gabriela, Santacruz; Paola, Arevalo; Alex, Valencia; Griselle, Anaya; Cesar, Avalos; Yadira, Toalongo; Francis, Avalos; Oswaldo, Tamayo; et al. (New Frontiers in Medicine and Medical Research Vol. 11, 2021)
Introduction: The first cases of Covid-19 disease were reported in December 2019.In March 2021, the pandemic had expanded worldwide, with 114.217.365 cases and 2.533014 deaths, including 286.155 cases and 15.811 deaths in Ecuador.The goal of this study was to share the impact of COVID-19 disease on 700 chronic dialysis patients from Ecuador's highlands, representing nearly 7% of the country's dialysis population, after one year of pandemic. Materials and Methods: An observational prospective multicenter study was conducted on 700 Latino chronic dialysis patients from five distinct cities in Ecuador's highlands.Patients were tracked from February 1, 2020, through January 31, 2021. Patients with COVID-19 symptoms were found, and the disease was diagnosed only through PCR testing of nasopharyngeal swabs. Disease presentation was defined as severe if oxygen saturation was less than 90% at presentation (LOS), moderate if symptoms were present but not at LOS, and asymptomatic if no symptoms were observed. The length of stay in the hospital, the period until a negative PCR, death, and laboratory results were all recorded. Results: Two hundred and five patients (29%) had COVID-19 illness symptoms; 115 patients (16%) tested positive, and 60 percent of them were men (p=0.03). Twenty-five patients passed away (22 percent ).Mortality was linked to being over 64 years old, having a saturation of less than 90%, and having a severe illness presentation (p=0.03), as well as having previous pulmonary pathology and hospitalisation (p=0.01). Hospitalization was needed in 74 patients (64%) with hospital stay 11 days (4-15), days until death during hospitalization of 12 days (4-19) and time until negative PCR 20 days (10-25). The duration of symptomatology was 16 days (11-26). Conclusion: COVID-19 disease was more common in men, and it has resulted in an additional 22% death rate in the chronic dialysis population. Patients over the age of 64, those with prior pulmonary disease, and those with a longer LOS at presentation are at a higher risk of mortality, necessitating more frequent follow-up in this subgroup. COVID-19 causes a high level of health care burden in the dialysis community, implying that dialysis patients and professionals involved in their treatment should be included in vaccination programmes to reduce disease-related mortality, infections, and health-care costs.